Bad animals, techno-fixes, and the environmental narratives of alternative protein - Hedberg, Russell C. (Frontiers in Sustainable Food Systems, 2023)
In the last decade animal agriculture has received significant scrutiny for its many negative environmental consequences, including nutrient pollution, resource use intensity, greenhouse gas emissions, and animal cruelty, among others. In response to these myriad concerns a wide range of voices have advocated for diets that include less animal products (meat, dairy, eggs), often arguing that animal-based diets are inherently more resource intensive than those based on plants. While academics have begun to scrutinize these arguments, they have been widely accepted in popular discourse, giving rise to a narrative that places blame on livestock and meat consumption rather than the system that produces it for profit. Amid this lack of criticism, a slew of venture capital-backed food technology startups have launched to produce animal product alternatives that can satisfy consumer demand while also solving one of the fundamental environmental challenges of modern agriculture. In this paper I draw on frameworks from political ecology, science and technology studies, and agroecology in the pursuit of two goals: (1) to give strict scrutiny to the environmental claims made by VC-backed protein alternatives, and (2) to examine the extent to which these ventures have shaped popular environmental narratives on sustainable agriculture that subtly favor the capitalist/industrial food system and obscure ecologically based and socially just food futures in which livestock will likely play an important role.